High Volumetric Energy Density Sulfur Cathode with Heavy and Catalytic Metal Oxide Host for Lithium–Sulfur Battery - Liu, Ya‐Tao; Liu, Sheng; Li, Guo‐Ran; Yan, Tian‐Ying; Gao, Xue‐Ping (Advanced science, 2020)
For high‐energy lithium–sulfur batteries, the poor volumetric energy density is a bottleneck as compared with lithium–ion batteries, due to the low density of both the sulfur active material and sulfur host. Herein, in order to enhance the volumetric energy density of sulfur cathode, a universal approach is proposed to fabricate a compact sulfur cathode with dense materials as sulfur host, instead of the old‐fashioned lightweight carbon nanomaterials. Based on this strategy, heavy lanthanum strontium manganese oxide (La0.8Sr0.2MnO3), with a high theoretical density of up to 6.5 g cm−3, is introduced as sulfur host. Meanwhile, the La0.8Sr0.2MnO3 host also acts as an efficient electrocatalyst to accelerate the diffusion, adsorption, and redox dynamics of lithium polysulfides in the charge–discharge processes. As a result, such S/La0.8Sr0.2MnO3 cathode presents high gravimetric/volumetric capacity and outstanding cycling stability. Moreover, an ultra‐high volumetric energy density of 2727 Wh L−1‐cathode is achieved based on the densification effect with higher density (1.69 g cm−3), which is competitive to the Ni‐rich oxide cathode (1800–2160 Wh L−1) of lithium–ion batteries. The current study opens up a path for constructing high volumetric capacity sulfur cathode with heavy and catalytic host toward practical applications of lithium–sulfur batteries. Heavy metal oxides are more suitable than light carbon materials to fabricate compact cathode for lithium–sulfur batteries. Specifically, lanthanum strontium manganese oxide nanofibers, with the tap density of 2.59 g cm−3, display efficient catalytic activity toward lithium polysulfides, enhancing the volumetric energy density of sulfur cathode, which can even exceed lithium–ion batteries.